Answer:
B
Explanation:
Given y = f(x) then
y = f(x ± a) represents a horizontal translation parallel to the x- axis.
• If + a then a shift of a units left ←
• If - a then a shift of a units right →
Here f(x) is translated 6 units left ⇒ f(x + 6)
--------------------------------------------------------------------
Given y = f(x) then
y = f(x) ± c represents a vertical translation parallel to the y- axis.
• If + c then a vertical translation up ↑
• If - c then a vertical translation down ↓
Here f(x) is translated 4 units up ⇒ f(x) + 4
----------------------------------------------------------------------
Combining the 2 translations gives
y = f(x + 6) + 4 → B